2019
DOI: 10.1542/hpeds.2018-0118
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound for the Pediatric Hospitalist’s Practice

Abstract: Point-of-care ultrasound (POCUS) has the potential to provide real-time valuable information that could alter diagnosis, treatment, and management practices in pediatric hospital medicine. We review the existing pediatric POCUS literature to identify potential clinical applications within the scope of pediatric hospital medicine. Diagnostic point-of-care applications most relevant to the pediatric hospitalist include lung ultrasound for pneumothorax, pleural effusion, pneumonia, and bronchiolitis; cardiac ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 120 publications
0
20
0
1
Order By: Relevance
“…Supporting this notion, family medicine is also heavily outpatient and clinical practice overlaps with pediatrics, yet other studies have found that graduates from family medicine programs where POCUS is taught continue to use POCUS in their clinical practice (31). Prior review articles on pediatric POCUS have focused on the role of POCUS in the practice of the pediatric hospitalist (1,11,(15)(16)(17)32). However, the majority of pediatric residents in our study were interested in POCUS, and over half of them planned to practice outpatient general pediatrics.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Supporting this notion, family medicine is also heavily outpatient and clinical practice overlaps with pediatrics, yet other studies have found that graduates from family medicine programs where POCUS is taught continue to use POCUS in their clinical practice (31). Prior review articles on pediatric POCUS have focused on the role of POCUS in the practice of the pediatric hospitalist (1,11,(15)(16)(17)32). However, the majority of pediatric residents in our study were interested in POCUS, and over half of them planned to practice outpatient general pediatrics.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, pediatricians ranked neck (lymph node vs abscess), advanced abdominal (appendicitis, intussusception, hypertrophic pyloric stenosis, cholecystitis) among the most useful diagnostic applications. These studies tend to be considered more advanced by POCUS experts (11,15). While the POCUS literature for pediatric appendicitis (34,35) and intussusception(36, 37) is growing, there is currently limited evidence to support the use of POCUS for differentiation of neck masses (3,38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anteroposterior chest radiographs can overlooked quite a number of effusion cases that can be detected by CT scan and ultrasonography. Pleural effusion is often misinterpreted as parenchymal opacity (Soni et al, 2015) Although CT scan is the gold standard for the diagnosis of pleural effusion, ultrasonography shows similar accuracy of sensiti-vity and specificity (Kurian et al, 2009;Hopkins et al, 2019) The ability of lung ultrasonography to identify complex effusions in pediatric patients correlates with chest radiograph and CT scan (k= 1,0) (Hopkins et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…Bedside ultrasound allows diagnostic, therapeutic and monitoring approaches in critically ill patients (1). Currently, ultrasound enables to perform almost a scan of all body regions in both adult and pediatric populations (2,3).…”
Section: Introductionmentioning
confidence: 99%